2009
DOI: 10.1111/j.1439-0531.2009.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of SCNT Buffalo (Bubalus bubalis) Embryos in Different Culture Medium and Analysis of mRNA Expression of Insulin-like Growth Factors During Embryogenesis

Abstract: Growth factors in culture media are known to affect the embryo production rates in in vitro production cultures. To improve the efficiency of somatic cell nuclear transfer (SCNT) derived embryos in Indian buffaloes (Bubalus bubalis), embryos were cultured in three different culture mediums viz. Group-A; TCM-199 + FBS, Group-B; TCM-199 + Poly vinyl alcohol (PVA) and Group-C; CR1aa + BSA. Embryo production rate and expression level of insulin-like growth factor genes (IGF-1, IGF-1R, IGF-2 and IGF-2R) were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
3
4
0
Order By: Relevance
“…For instance, Han et al (2003) described that bovine SCNT blastocysts have increased expression of IGF2 compared to IVF blastocysts. Furthermore, these authors demonstrated that IGF2 expression was greater in the SCNT embryos cultured in serum containing medium, suggesting that the presence of exogenous proteins in the culture medium aff ected critical development points (Pandey et al, 2010). In agreement with some previous fi ndings, the low expression of IGF2 observed in our bovine SCNT embryos cultured in K-S/BSA medium could be responsible for the low pre-implantation development observed presently.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Han et al (2003) described that bovine SCNT blastocysts have increased expression of IGF2 compared to IVF blastocysts. Furthermore, these authors demonstrated that IGF2 expression was greater in the SCNT embryos cultured in serum containing medium, suggesting that the presence of exogenous proteins in the culture medium aff ected critical development points (Pandey et al, 2010). In agreement with some previous fi ndings, the low expression of IGF2 observed in our bovine SCNT embryos cultured in K-S/BSA medium could be responsible for the low pre-implantation development observed presently.…”
Section: Discussionsupporting
confidence: 91%
“…IGF-2R mRNA levels in 2-cell, 4-cell, and hatched blastocysts cultured in serum free-defined medium were higher (P \ 0.05) that for undefined media-containing serum. Culture conditions of embryos, particularly the presence of serum in culture medium, could affect expression of this gene, as observed previously by Fernández-Gonzalez et al (2009) in mouse andPandey et al (2010) in buffalo SCNT. Giraldo et al (2008) reported that abnormal pattern of transcript may be due to epigenetic modifications due to culture conditions, which directly affect chromatin remodelling and is correlated to imprinted genes.…”
Section: Discussionsupporting
confidence: 56%
“…This study is potentially based on the assumption that the expression of genes related to stress response, such as HSPS can also be influenced by inadequate culture conditions (Christians et al. 1997; Pandey et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We chose HSPA-1A as target gene to analyse early bubaline embryonic response to thermal and other intercellular environmental stress in pre-implantation development, because HSPA-1A is synthesized not only in response to stress but also functions as molecular chaperon. This study is potentially based on the assumption that the expression of genes related to stress response, such as HSPS can also be influenced by inadequate culture conditions (Christians et al 1997;Pandey et al 2010). Findings of this study demonstrate the higher level of HSPA-1A in IVP embryos as compared to IVD group, suggesting stress on embryos during in vitro culture environment.…”
Section: Discussionmentioning
confidence: 99%